Ayurvedic Management of Comorbid State of Autism with Attention Deficit Hyperactivity Disorder w.s.r Unmada (AYUSHDHARA, 2023)
Unmada a term used in Ayurveda, refers to a condition characterized by mental instability, restlessness and abnormal behaviors. It similar to modern day autism spectrum disorder (ASD) and attention deficit hyperactive disorder (ADHD). ASD and ADHD are neuro developmental and neuropsychiatric disorder. These disorders have shared genetic heritability and are both associated with shared impairment in social functioning and executive functioning. However, in the phenotypic presentation of the impairment which characterized ASD and ADHD. The fundamental principles of Ayuvedic management are to restore the balance of the Doshas. In the case of Unmada, particularly when comorbid with autism and ADHD, the focus on pacifying the aggravated Vata dosha. This can be achieved through a combination of dietary modification, lifestyle changed, Balpanchkarma and Marma therapies and Medhya Dravya. Aim and Objective: A case study of Ayurvedic management of comorbid state of Autism and Attention Deficit Hyperactivity Disorder w.s.r Unmaad. Material and Method: A 5-year-old female patient was come to the OPD of Kaumarbhritya Department, Rishikul Campus, UAU, Haridwar. With complain of difficulty in speaking as per development age, poor eye contact, hyperactive in nature with addiction of mobile in the last three year. This condition can be understood as Unmada. Treatment including with some Balpanchkarma and Marma therapies, and Ayurvedic formulations for 2-3 months. Result: There significant improvement in the condition of the patient. Ayurvedic intervention in this case reveals the true potential and efficacy of our Ayurvedic science.